Advances in artificial intelligence, software and systems engineering : proceedings of the AHFE 2019 International Conference on Human Factors in Artificial Intelligence and Social Computing, the AHFE International Conference on Human Factors, Software, Service and Systems Engineering, and the AHFE International Conference of Human Factors in Energy, July 24-28, 2019, Washington D.C., USA.: proceedings of the AHFE 2019 International Conference on Human Factors in Artificial Intelligence and Social Computing, the AHFE International Conference on Human Factors, Software, Service and Systems Engineering, and the AHFE International Conference of Human Factors in Energy, July 24-28, 2019, Washington D.C., USA. ([2020]) - Unknown
No abstract available